Analisis Kitab Riyadhul Sholihin Terhadap Gaya Busana Muslimah Masa Kini - Eka Hujaemah; Indah Sartika Putri; Rina Pujawati; Afif Nurseha (UIN Fatmawati Sukarno Bengkulu, 2025)
This research is related to the analysis of Riyadhu Shohlihin's book about contemporary Muslim women's fashion styles. Riyadhu Shohlihin is a book that contains interpretations of verses from the Koran regarding Muslim women's clothing. This analysis was carried out to find out whether the concept of Muslim women's clothing in the Al-Qur'an still applies to current reality and to search for truth that is adapted to current reality. This research uses library research methods by collecting data from tafsis books and books related to this topic. The results of the analysis show that the Al-Qur'an's teachings regarding Muslim women's clothing, especially in terms of the hijab, jilbab and khimar, can be adapted to the context of modern women along with the adaptation of early Muslim society. This adaptation can be proven if the text is interpreted by taking into account the social context of Islamic society with social and contemporary changes. This analysis also shows that today's Muslim women's clothing styles tend to be tight and shape the curves of the body. deviating from Islamic law which recommends that Muslim women dress to cover their private parts. Therefore, this research hopes to contribute to a deeper understanding of Muslim women's clothing and how the teachings of the Koran can adapt to current realities.